Analisis Keuntungan dan Kelayakan Usahatani Padi Sawah di Kecamatan Konda Kabupaten Konawe Selatan - Haerudin Tao; La Ode Geo; Muhammad Arief Dirgantoro (Universitas Halu Oleo, 2019)
This study aims to determine the benefits and feasibility of lowland rice farming in Konda District, Konawe Selatan Regency. The population in this study is all lowland rice farmers. The samples were determined by cluster random sampling with a total sample of 60 farmers. Data were collected by interview method, and data collected included: costs, production, and revenue of lowland rice farming. The results of the study show that the benefits of lowland rice farming are relatively small, and the value of revenue/cost (R/C), both the R/C of the explicit cost and the R/C of the total cost is greater than 1 (one), which means that lowland rice farming is feasible.Keywords: profit; feasibility; farming; paddy